Corporate reputation in a public university that trains social workers in public health (GEON Journal (Management, Organizations and Business), 2022)
Problematic: in a context of risk, the reputation of an organization is affected by the expectations of its members. Consequently, the prestige of the organization is a function of the future needs of its members, when they converge on a common purpose and task. Objectives: to establish the structure of expectations around the reputation of a higher education institution (HEI), comparing the literature review with the responses to a survey. Materials and methods: an exploratory, cross-sectional and psychometric study was carried out with a sample of 100 students. Results: the structure of seven factors was established (follow-up, adherence, counseling, interview, mediation, promotion and follow-up) that supported 82% of the total variance explained. In other words, corporate reputation is explained through the relationship between these seven factors, as they clarify the internal and external expectations of the public institution. Discussion: the study's contribution to the state of knowledge lies in the testing of a structural equation model to explain corporate reputation in a public university. The seven established factors follow the same relationships reported in the selected literature, although the percentage of the variance explained suggests the inclusion of an eighth factor, identified as corporate image. These are expectations external to the institution that place it in accordance with the medium-term objectives. Conclusion: corporate reputation is linked to accompaniment as a preponderant factor. It means, then, that both internally and externally the university is distinguished by its degree of attention and monitoring of academic rights. Consequently, educational policies can be evaluated from corporate reputation as an indicator of participation and governance. Contribution / originality: the reliability and validity of an instrument that measured seven dimensions of corporate reputation was established.
Keywords: Counseling; politics and social welfare; social and human sciences; social work; volunterering; Z180 Cultural Economics: Public Policy